The Hunt in Sansho Dayu (1915) and L’Oiseau bleu by Maurice Maeterlinck - Terrón Barbosa, Lourdes de los Ángeles (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The origins of the legend of Anju and Zushio, children cruelly torn from their mother and sold to Sansho, are lost in the Middle Ages, but it was “Ôgai” Mori Rintarô who gave it literary status when he published the historical tale Sansho dayu in 1915. The analysis details the important symbolic role played by birds in freedom and the hunting of birds. The bird, symbol of freedom and autonomy. In parallel, an antagonism, the hunting of birds. Death and the bird complement a bipolarity of symbolic content present throughout the work.